Dispersão da febre amarela entre primatas não-humanos durante epizootia no Rio Grande do Sul : entendendo o papel de fatores abióticos, da paisagem e da presença de animais imunes para propor cenários futuros de reemergência da doença - Almeida, Marco Antônio Barreto de (2018)
Nonhuman primates (NHP) are susceptible to many arboviruses, including the yellow fever (YF) virus. Although native to Africa, this virus found susceptible NHP and competent mosquito vectors for maintaining its transmission in American forests. A high sensitivity of NHP to YF led health agencies to monitor these animals as a way of monitoring the disease in Brazil. The State of Rio Grande do Sul (RS) began this surveillance in 2002, which has detected the arboviruses Oropouche and Saint Louis (SLEV) and a YF epizootic that killed more than 2,000 NHP (Alouatta caraya and A. guariba clamitans) between 2008 and 2009. The objectives of this PhD thesis research were to generate models of niche suitability for YF based on that epizootic and prospect arboviruses in NHP in northwestern RS. The maximum entropy algorithm - Maxent was used to generate distribution models of Alouatta spp. and the mosquito vector Haemagogus leucocelaenus. Together with climatic, topographic and vegetative variables, these models served as predictor layers to model the occurrence of the disease based on the points of death of NHP of YF. The most influential variables in the YF models were the variation in air humidity, distribution of Alouatta spp. and maximum wind speed followed by mean annual rainfall and maximum temperature. Therefore, support for the influence of the rainfall regime and the ambient temperature on the cycle of jungle YF was found. Wind speed and direction can play an important role in the dispersal of infected mosquitoes and, consequently, the virus. The models based on the occurrence of dead NHP in the first months of the epizootic identified suitable areas to where the disease spread a few months later. In addition, 19 arboviruses were prospected in 40 blood (viral isolation and PCR) and serum (hemagglutination inhibition and neutralization tests [NT]) samples collected from 26 black howler monkeys (A. caraya) belonging to three populations in four field campaigns in the municipality of Santo Antônio das Missões, RS, between 2014 and 2016. There was no detection of circulating virus, but antibodies to Flavivirus SLEV and Ilhéus and Phlebovirus Icoaraci was found by NT. Evidence of the contact with Ilhéus and Icoaraci are the southernmost records in Brazilian NHP. An increase in antibodies to SLEV detected between two consecutive captures of the same individual is compatible with a recent contact with the virus. An adult male captured in one of the areas presented concomitant infection by the Oropouche, SLEV and YF viruses by NT. Further studies are necessary to understand the role played by NHP and other vertebrates in the circulation of arboviruses in the region, to assess potential risks to NHP and public health, and to identify the driving forces responsible for the dispersal of the YF virus during epizootics in wildlife populations.